(untitled) (مجلة الواحات للبحوث والدراسات, 2025)
The present study aimed to analyse the level of social skills among educational personnel in the municipality of Sebseb, Ghardaïa. The investigation encompassed a total population (n = 88) of educational staff—including principals, teachers, and superintendents —comprising 30 males and 58 females, all of whom were assessed via exhaustive sampling. Employing a descriptive research design consonant with the study’s objectives, data were gathered using the Social Skills Scale developed by Nasr-El-Din Abdel-Hamid (2011). Statistical analyses were conducted with the Social Sciences Statistical Package (SPSS), utilising frequency distributions, percentages, arithmetic mean, and standard deviation as primary techniques,results indicated that: • The overall level of social skills among the educational personnel in Sebseb municipality is high. • No statistically significant differences in social skills levels were observed across gender. • No statistically significant differences in social skills levels were observed across age groups. • No statistically significant differences in social skills levels were observed across varying lengths of professional experience. • No statistically significant differences in social skills levels were observed across different workplace settings. • No statistically significant differences in social skills levels were observed across types of educational roles. Keywords: social skills level; educational personnel .